Composite reinforced modifier for anticorrosive paint and preparation method thereof

Through the combination of composite modified nanocellulose and modified mica nanosheets, the problem of poor dispersion of mica nanosheets is solved, and the mechanical and corrosion resistance of anticorrosion coatings are significantly improved to form a solid protective film.

CN119264717AActive Publication Date: 2025-01-07中科纳美(天津)生物工程有限公司 +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411692733.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The dispersion of mica nanosheets in existing anticorrosion coatings is poor, resulting in their agglomeration in the paint film, affecting the mechanical properties and corrosion resistance of the anticorrosion coatings.

Method used

Modified mica nanosheets were prepared by combining composite modified nanocellulose and modified mica nanosheets, and then combined with composite modified nanosheets were prepared by high-temperature calcination, acidification, lithiation, intercalation modification and ultrasonic peeling. The cellulose is mixed to form a composite reinforcement modifier, improving the mechanical properties and corrosion resistance of the paint film.

Benefits of technology

The mechanical properties and corrosion resistance of the paint film are significantly improved. The modified mica nanosheets are evenly dispersed in the paint film to form a solid chemical corrosion-resistant and sunlight radiation protection film, enhancing the barrier protection of the substrate material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264717A_ABST
    Figure CN119264717A_ABST
Patent Text Reader

Abstract

The invention provides a composite reinforced modifier for anticorrosive paint and a preparation method thereof, and the preparation method comprises the following steps: mixing composite modified nanocellulose, modified mica nanosheets, a nonionic surfactant and deionized water to obtain a composite suspension liquid, carrying out ultrasonic dispersion on the composite suspension liquid to obtain a composite dispersion liquid, and drying the composite dispersion liquid to obtain the composite reinforced modifier for anticorrosive paint. And carrying out spray drying on the composite dispersion liquid to obtain the composite reinforced modifier. The composite reinforced modifier for the anticorrosive paint is prepared by compounding the composite modified nanocellulose and the mica nanosheets, and the mechanical property and the corrosion resistance of the anticorrosive paint can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-corrosion coatings and relates to a composite reinforcing modifier for anti-corrosion coatings and a preparation method thereof. Background Art

[0002] With the continuous development of industries such as steel, metallurgy, and machinery manufacturing, the corrosion problem has become increasingly serious, which has brought huge crises to the development of the national economy, people's lives, and the social environment. Therefore, anti-corrosion and consumption reduction issues have attracted widespread attention from all departments, and solving the anti-corrosion problem is imperative.

[0003] Adding reinforcing modifiers to anti-corrosion coatings is a very effective anti-corrosion modification method, which has attracted widespread attention from domestic and foreign scholars. For anti-corrosion coatings, good electrical resistance and water (chemical) resistance are the most fundamental requirements. How to improve their electrical resistance and water (chemical) resistance has become a hot topic for many scientific researchers.

[0004] Adding flaky fillers to anti-corrosion coatings is an effective modification method. As a flaky filler, sericite is not easily destroyed during the grinding process. Adding mica nanosheets to anti-corrosion coatings can prevent the diffusion of small molecules such as water and oxygen on the one hand; on the other hand, it can effectively block the erosion of chemicals, increase corrosion resistance, increase surface hardness, and improve acid washing resistance, playing a good protective role. However, sericite, like other inorganic non-metallic mineral fillers, has hydrophilic and oleophobic properties, so it is difficult to wet and disperse in the organic phase, and it cannot form a good interface with the resin emulsion, resulting in uneven dispersion in the anti-corrosion coating and easy agglomeration. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite reinforcing modifier for anti-corrosion coatings and a preparation method thereof. The present invention compounded composite modified nanocellulose and mica nanosheets to prepare a composite reinforcing modifier for anti-corrosion coatings, which can significantly improve the mechanical properties and corrosion resistance of the paint film.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a composite reinforcing modifier for an anti-corrosion coating, the preparation method comprising:

[0008] (I) mixing nanocellulose and N,N'-carbonyldiimidazole solution, stirring and heating to react, and obtaining an intermediate product solution after the reaction is completed; adding octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose; dispersing the modified nanocellulose in dopamine solution, mixing, stirring and heating to react, and centrifuging, washing and freeze-drying after the reaction is completed to obtain composite modified nanocellulose;

[0009] (II) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets; subjecting the mica nanosheets to surface hydrophobic modification with a silane coupling agent to obtain modified mica nanosheets;

[0010] (III) mixing the composite modified nanocellulose obtained in step (I), the modified mica nanosheets obtained in step (II), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the composite reinforcing modifier.

[0011] The present invention compounds composite modified nanocellulose and modified mica nanosheets to prepare a composite reinforcing modifier for anticorrosive coatings, which can significantly improve the mechanical properties and corrosion resistance of the paint film. In the anticorrosive coating, the modified mica nanosheets tend to be arranged parallel to the paint film surface. Since the modified mica nanosheets are sheet-like structures, they are elastic and can slide, and can form a layer of inert, solid and flexible protective film on the paint film surface that resists chemical corrosion and sunlight radiation. This protective film can effectively prevent the penetration of atmosphere and moisture, thereby playing a barrier and protective role on the base material. Combined with the mechanical enhancement characteristics of the composite modified nanocellulose itself, on the one hand, a three-dimensional network structure skeleton can be formed inside the paint film, and on the other hand, the dispersion uniformity of the modified mica nanosheets in the anticorrosive coating can be significantly improved, and the mechanical properties and corrosion resistance of the paint film can be significantly improved through the synergistic effect between the composite modified nanocellulose and the modified mica nanosheets.

[0012] In the present invention, the composite modified nanocellulose can significantly improve the uniformity of the dispersion of modified mica nanosheets in the anticorrosive coating. This is because, on the one hand, the composite modified nanocellulose is a fibrous filamentous structure with a large specific surface area and a high aspect ratio, which can form a three-dimensional network structure skeleton in the paint film after being added. When the modified mica nanosheets are uniformly loaded on the three-dimensional network structure skeleton, the composite modified nanocellulose can become a "physical bridge" between the modified mica nanosheets. When subjected to external forces, the load stress can be smoothly transferred to avoid stress concentration leading to paint film rupture; on the other hand, Since the modified mica nanosheets are modified with silane coupling agents, their surfaces contain some silicon hydroxyl groups, which can combine with the large number of free hydroxyl groups on the surface of the composite modified nanocellulose to produce strong hydrogen bonding. There is also hydrogen bonding between the composite modified nanocellulose and the resin emulsion. Therefore, the composite modified nanocellulose can also serve as a "chemical bridge" between the resin emulsion and the modified mica nanosheets. Through the dual effects of "physical bridge" and "chemical bridge", the dispersion uniformity of the modified mica nanosheets in the anti-corrosion coating is greatly improved, thereby significantly improving the mechanical properties and corrosion resistance of the paint film.

[0013] The present invention uses nanocellulose as a film-forming material and a mechanical reinforcement material and adds it to the anticorrosive coating, which can significantly improve the rheological properties of the anticorrosive coating and the mechanical properties of the paint film. On the one hand, there are a large number of exposed hydroxyl functional groups on the surface of nanocellulose, which can form hydrogen bonds with the resin emulsion in the anticorrosive coating; at the same time, strong hydrogen bonding will also occur between the nanocelluloses, so that the nanocelluloses are cross-linked to form a stable three-dimensional network structure, which can give the anticorrosive coating excellent rheological properties. The three-dimensional network structure formed by hydrogen bonding is temporarily destroyed under the action of shear force, resulting in a decrease in the viscosity of the anticorrosive coating. When the shear force is removed, the three-dimensional network structure will be re-formed, and the viscosity of the anticorrosive coating will increase again, so that the anticorrosive coating presents rheological characteristics and has a shear-thinning effect, which can be used to improve the sedimentation of the coating during storage and the pseudoplastic characteristics during construction. On the other hand, since nanocellulose has crystalline and non-crystalline regions along the length of the cellulose molecular chain, the crystalline region has a larger density and has natural hydrophobic properties. The three-dimensional hydrogen bond network structure formed between and within nanocellulose molecules gives the paint film a higher mechanical strength, which can significantly improve the hardness and washing resistance of the paint film.

[0014] Since nanocellulose molecules contain a large number of hydroxyl groups and have strong intermolecular hydrogen bonds, they are very prone to agglomeration. In particular, hydrogen bond closure during the drying process will cause irreversible fiber keratinization, which causes serious agglomeration of nanocellulose after drying and makes it difficult to redisperse it by physical methods. In order to improve the dispersion uniformity and stability of nanocellulose in anti-corrosion coatings, the present invention uses N, N′-carbonyldiimidazole (CDI) and octadecylamine to hydrophobically modify nanocellulose.

[0015] N, N'-carbonyldiimidazole (CDI) is a derivative of imidazole, and its imidazole structure has a closed large P bond, and one of the nitrogen atoms has a pair of lone electrons in the unbonded sp2 orbital. These characteristics determine that CDI has strong chemical reactivity and can react with functional groups such as amino, carboxyl and hydroxyl groups. The present invention adopts a CDI-amino grafting modification method to hydrophobically modify nanocellulose to obtain modified nanocellulose, and one of the imidazole structures on the CDI molecular chain reacts with the hydroxyl group on the nanocellulose molecular chain to form an ester imidazole structure on the nanocellulose molecular chain, and then another imidazole structure on the CDI molecular chain reacts with the amino group on the octadecylamine molecular chain to form a carbamate bond between the octadecylamine molecular chain and the nanocellulose molecular chain, so that the octadecylamine molecular chain is firmly grafted onto the nanocellulose molecular chain.

[0016] The CDI-amino modification method provided by the present invention can significantly improve the hydrophobicity of nanocellulose, thereby greatly improving the uniformity of dispersion of nanocellulose in anticorrosive coatings, and at the same time, can further enhance the mechanical enhancement of nanocellulose. This is because octadecylamine is a low surface energy substance containing long-chain alkyl and active amino groups. The amino group in octadecylamine and the imidazole structure on the CDI molecular chain can graft the hydrophobic long chain of octadecylamine on the surface of nanocellulose to give it hydrophobicity. The low surface energy octadecylamine molecular chain can also significantly improve the dispersibility of nanocellulose, thereby reducing the agglomeration of nanocellulose; at the same time, the brush-like structure formed by the octadecylamine molecular chain on the surface of nanocellulose can also effectively avoid the flocculation of nanocellulose, and promote the formation of nanocellulose reinforcement network, thanks to the uniform dispersion of nanocellulose in anticorrosive coatings and the formation of reinforcement network, so that the mechanical properties of the paint film are significantly enhanced. In addition, thanks to the excellent chemical stability of the carbamate bond, it has good tolerance to acidic and alkaline environments, and the hydrophobic durability of the paint film finally formed is also significantly improved.

[0017] In order to further improve the dispersion stability of modified nanocellulose in anticorrosive coatings, the present invention adds dopamine modification treatment on the basis of CDI-amino grafting modification method. Dopamine can undergo self-polymerization under aerobic weak alkaline conditions to generate a viscous substance polydopamine. After dopamine is oxidized to dopamine quinone, it is easy to undergo Michael addition reaction or Schiff base reaction with organic molecules containing amino, thiol or imino groups. Based on this, the present invention first grafts octadecylamine long chains on the surface of nanocellulose through CDI-amino grafting modification method to obtain modified nanocellulose, and then uses dopamine oxidation self-polymerization to modify the modified nanocellulose to obtain composite modified nanocellulose.

[0018] The purpose of dopamine modification is that, on the one hand, the hydrophobic long chain of octadecylamine can significantly reduce the surface energy of modified nanocellulose, and the hydrophobic long chain of octadecylamine can be reinforced by the adhesion of polydopamine, which can ensure that the hydrophobic long chain of octadecylamine is wear-resistant and not easy to fall off, maintain the long-term hydrophobicity of the paint film, and make the paint film still have good hydrophobicity after hundreds of frictions; on the other hand, polydopamine can react with octadecylamine to form a Schiff base reaction, and adsorb the free octadecylamine in the solution on the surface of modified nanocellulose through its own adhesion, thereby constructing a rough structure on the surface of modified nanocellulose. Through the synergistic effect between dopamine and octadecylamine, the surface energy of modified nanocellulose can be further reduced and a large number of rough structures can be constructed, thereby significantly improving the dispersion stability of modified nanocellulose in anticorrosive coatings.

[0019] Mica nanosheets are a two-dimensional flaky filler. After adding an appropriate amount of mica nanosheets to the anti-corrosion coating, the barrier property of the paint film can be significantly improved to provide good corrosion resistance. The present invention uses sericite as a raw material, and obtains mica nanosheets through high-temperature activation, acidification, lithiation, intercalation modification and ultrasonic stripping. However, due to the hydrophilicity of mica nanosheets, the dispersibility in the anti-corrosion coating is poor, and it is easy to agglomerate in the anti-corrosion coating, which hinders the advantages of mica nanosheets in the paint film. For this reason, the present invention hydrophobically modifies the mica nanosheets to improve their uniformity of dispersion in the anti-corrosion coating.

[0020] Sericite is a silicate mineral with a layered structure. During the high-temperature activation process, the OH - Desorption and conversion into interlayer water. During the calcination process, the temperature difference between the inside and outside of the sericite flakes is large, resulting in a large temperature gradient between the middle and edge areas of the flakes. The interlayer water discharge rate in the edge area is faster, and the water is enriched around the sericite, sealing the internal space between the layers of the sericite. Water loss and sealing occurs in the edge area of ​​the sericite flakes, making it difficult to discharge the water in the middle area of ​​the layer, resulting in a higher vapor pressure in the middle area of ​​the layer, forcing the sericite flakes to expand, which is beneficial to the subsequent organic intercalation treatment of hexadecyltrimethylammonium bromide.

[0021] The physical and chemical structure of sericite is composed of two layers of silicon-oxygen tetrahedron [(Si,Al)-O 4 ] and the middle layer of aluminum oxide octahedron [AlO 2 (OH) 4] The interlayer cations are mainly potassium ions and magnesium ions. Since potassium ions and magnesium ions have larger ion radius, higher charge density and larger ion hydration number, there are more water molecules around potassium ions and magnesium ions and they are more firmly bound, which makes potassium ions and magnesium ions lose their ion exchange capacity, which is not conducive to organic intercalation modification. At the same time, potassium ions are just embedded in two hexagonal meshes facing each other on adjacent crystal planes, forming 12 times coordination, and the interlayer charge is close to neutrality. The potassium ions are very tightly bound to the crystal planes, and the interlayer spacing is relatively fixed, which makes the exchangeable ion concentration of sericite low and the interlayer charge very stable. Even if the sheets expand after high-temperature activation, due to the weak ion exchange capacity, it is difficult for hexadecyltrimethylammonium bromide to enter the interlayers of sericite through ion exchange for intercalation modification. To this end, the present invention performs acidification and lithiation treatment on the sericite after high-temperature activation, thereby increasing the interlamellar spacing of the sericite through high-temperature activation and increasing the exchangeable ion concentration between the sericite lamellae through acidification and lithiation, thereby greatly promoting the organic intercalation modification of hexadecyltrimethylammonium bromide.

[0022] Since Al-O tetrahedron is not as stable as Si-O tetrahedron, acid treatment of sericite can destroy Al-O tetrahedron, preferentially dissolve Al in tetrahedron and deplete it, thus destroying interlayer ionization balance and enhancing interlayer activity. 3 O + It can replace most of the interlayer magnesium ions and dissolve a small amount of cations in the aluminum oxide octahedron, so that some impurities between the sericite sheets are dissolved by acid, the interlayer channels are unblocked, and the diffusion and adsorption capacity of molecules between the layers is improved. In addition, after acid treatment, a large number of fine grooves appear on the surface of the sericite sheets, which increases the surface roughness, ion adsorption area and surface electrical properties of the sericite, and improves the ion exchange capacity between the sericite sheets. After acid treatment, some interlayer ions such as aluminum ions, magnesium ions, calcium ions and potassium ions are dissolved, and the interlayer charge is destroyed. Subsequently, lithium treatment is performed to further improve the interlayer ion exchange capacity of sericite. Since the ion radius of lithium ions is relatively small, the charge density is low, the binding energy between the sheets of sericite is weak, the hydration energy is low, and the hydration ion radius is large, the cations are easier to exchange ions with the outside world, thereby increasing the exchangeable ion concentration between the sericite sheets, which is beneficial to organic intercalation modification.

[0023] Through the early high-temperature activation, acidification and lithiation treatment, the layers of sericite have exchangeable water molecules and cations. At this time, the concentration of exchangeable cations is relatively high, and the hexadecyltrimethylammonium bromide molecules can enter the layers of sericite through cation exchange to obtain intercalated sericite. When the ammonium ions in hexadecyltrimethylammonium bromide enter the sericite lamellae through ion exchange, the sericite lamellae are stretched open by the cleavage plane, and the alkyl chains then enter the lamellae. After entering the lamellae, hexadecyltrimethylammonium bromide adopts the most stable spatial form for arrangement. When the concentration of hexadecyltrimethylammonium bromide is low, the alkyl chains are arranged parallel to the lamellae surface. As the concentration of hexadecyltrimethylammonium bromide increases, the alkyl chains continue to enter the interlayers of sericite, the angle with the lamellae surface becomes larger, and the single layer is transformed into a double layer until the concentration of hexadecyltrimethylammonium bromide increases to form a double-layer structure and arrange at a large angle. Due to the spatial form and distribution of the alkyl chains between the sericite lamellae, the spacing between the sericite lamellae is forced to expand. Under the action of ultrasonic-assisted exfoliation, the overlapping lamellae of sericite are finally completely exfoliated to form mica nanosheets.

[0024] The present invention uses a silane coupling agent to hydrophobically modify mica nanosheets. The silane coupling agent is hydrolyzed under the action of deionized water to generate silanols. The generated silanols undergo a condensation reaction to form silane oligomers. The silane oligomers further react with hydroxyl groups on the surface of the mica nanosheets to generate silicon oxygen bonds after dehydration condensation, thereby being grafted on the surface of the mica nanosheets to achieve hydrophobic modification of the mica nanosheets. In addition, the mechanical enhancement effect of the modified mica nanosheets can be improved by modification with a silane coupling agent. This is because the silane coupling agent plays a cross-linking role between the modified mica nanosheets, so that the cross-linking density of the anti-corrosion coating to which the composite reinforcement modifier provided by the present invention is added increases, and cracks and holes on the surface and inside of the paint film are reduced, resulting in a denser surface of the paint film formed in the end, giving the paint film higher mechanical properties and corrosion resistance.

[0025] As a preferred technical solution of the present invention, in step (I), the N,N'-carbonyldiimidazole solution consists of N,N'-carbonyldiimidazole and dichloromethane.

[0026] In an optional example, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2~0.3 mol / L, for example, it can be 0.2mol / L, 0.21mol / L, 0.22mol / L, 0.23mol / L, 0.24mol / L, 0.25mol / L, 0.26mol / L, 0.27mol / L, 0.28mol / L, 0.29mol / L or 0.3mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In an optional example, the mass ratio of the nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1~1.2), for example, it can be 1:1.0, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In an optional example, the mixing and stirring time of the nanocellulose and the N,N'-carbonyldiimidazole solution is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In an optional example, the temperature for mixing and stirring the nanocellulose and the N,N'-carbonyldiimidazole solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In an optional example, in step (I), the octadecylamine solution consists of octadecylamine and dichloromethane.

[0031] In an optional example, the concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L, for example, it can be 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In an optional example, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1.1~1.2), for example, it can be 1:1.1, 1:1.11, 1:1.12, 1:1.13, 1:1.14, 1:1.15, 1:1.16, 1:1.17, 1:1.18, 1:1.19 or 1:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] The present invention particularly defines that the molar ratio of N,N'-carbonyldiimidazole in N,N'-carbonyldiimidazole solution to octadecylamine in octadecylamine solution is 1:(1.1-1.2). With the increase of the amount of octadecylamine, the hydrophobicity of the modified nanocellulose finally obtained increases first and then tends to be stable. This is because, with the increase of octadecylamine, the hydrophobic long chain of octadecylamine grafted onto the nanocellulose molecular chain increases, and the hydrophobicity increases accordingly. When the amount of octadecylamine used exceeds the upper limit of the range defined by the present invention, since the number of hydroxyl functional groups on the nanocellulose molecular chain is certain, the N,N'-carbonyldiimidazole that reacts with the hydroxyl functional groups is certain, so when octadecylamine is added in excess, the reaction of octadecylamine and N,N'-carbonyldiimidazole reaches saturation, and there is no imidazole structure that continues to react with octadecylamine. Continuing to increase the amount of octadecylamine will not lead to an increase in the grafting rate of octadecylamine, and the hydrophobicity of the modified nanocellulose finally obtained will not continue to increase.

[0034] In an optional example, the mixing and stirring time of the intermediate product solution and the octadecylamine solution is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] The present invention particularly limits the mixing and stirring time of the intermediate product solution and the octadecylamine solution to 10 to 12 hours. As the reaction time is prolonged, the hydrophobicity of the modified nanocellulose finally obtained first increases and then tends to be stable. This is because, when the reaction time is less than 10 hours, the reaction of the imidazole structure on the N,N'-carbonyldiimidazole molecular chain with the amino group on the octadecylamine molecular chain is not complete. At this time, there are still a large number of free octadecylamine molecules in the reaction system, and the number of octadecylamine molecules grafted onto the nanocellulose molecular chain is relatively small. When the reaction time reaches 12 hours, the reaction of the imidazole structure on the N,N'-carbonyldiimidazole molecular chain with the amino group on the octadecylamine molecular chain is complete. At this time, the number of octadecylamine grafted onto the nanocellulose molecular chain reaches a maximum value, the hydrophobicity reaches a maximum, and further extension of the reaction time will not lead to an increase in the grafting rate of octadecylamine, and the hydrophobicity will not continue to increase.

[0036] In an optional example, the temperature for mixing and stirring the intermediate product solution and the octadecylamine solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] The present invention particularly limits the mixing and stirring temperature of the intermediate product solution and the octadecylamine solution to 40-50°C. As the reaction temperature increases, the hydrophobicity of the modified nanocellulose finally obtained shows a trend of first increasing and then decreasing. This is because, when the reaction temperature is lower than 40°C, the octadecylamine has not yet completely melted, and there are still blocky octadecylamine solids in the reaction system. As the reaction temperature increases, the octadecylamine gradually melts, the reaction rate between N,N'-carbonyldiimidazole and octadecylamine gradually increases, the octadecylamine grafted onto the nanocellulose molecular chain gradually increases, and the hydrophobicity of the modified nanocellulose gradually increases; when the reaction temperature is higher than 50°C, the octadecylamine molecules grafted onto the nanocellulose dissolve and fall off due to the excessively high temperature, resulting in a further decrease in the hydrophobicity of the modified nanocellulose.

[0038] In an optional example, in step (I), the dopamine solution is prepared by the following method:

[0039] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1-2 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain the dopamine solution, wherein the concentration of the mixed solution can be 1.0 g / L, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L, 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L or 2.0 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Dopamine is easy to generate the adhesive substance polydopamine under weak alkaline conditions. Polydopamine can be deposited on the surface of modified nanocellulose through hydrogen bonds or covalent bonds. In addition, the catechol functional groups contained in dopamine can be oxidized into quinone structures and undergo Michael addition or Schiff base reactions with the amino groups in octadecylamine. Therefore, polydopamine can be used to reinforce the long hydrophobic chains of octadecylamine on the surface of modified nanocellulose, which can effectively prevent the octadecylamine molecular chains from falling off, so as to achieve a long-lasting hydrophobic effect.

[0041] The present invention particularly limits the concentration of dopamine in the mixed solution to 1-2 g / L. When the concentration of dopamine in the mixed solution is lower than 1 g / L, the generated polydopamine is insufficient to cover all the hydrophobic long chains of octadecylamine on the surface of the modified nanocellulose. When the concentration of dopamine in the mixed solution exceeds 2 g / L, desorption will occur when the concentration of dopamine in the mixed solution exceeds the equilibrium adsorption value.

[0042] In an optional example, the mass ratio of the modified nanocellulose to dopamine in the dopamine solution is 100:(8~10), for example, it can be 100:8.0, 100:8.2, 100:8.4, 100:8.6, 100:8.8, 100:9.0, 100:9.2, 100:9.4, 100:9.6, 100:9.8 or 100:10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In an optional embodiment, the mixing and stirring time of the modified nanocellulose and the dopamine solution is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In an optional embodiment, the temperature for mixing and stirring the modified nanocellulose and the dopamine solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In an optional example, the centrifugal rotation speed is 6000~8000r / min, for example, it can be 6000r / min, 6200r / min, 6400r / min, 6600r / min, 6800r / min, 7000r / min, 7200r / min, 7400r / min, 7600r / min, 7800r / min or 8000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In an optional example, the centrifugation time is 20 to 30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In an optional embodiment, the freeze-drying temperature is -50~-60°C, for example, it can be -50°C, -51°C, -52°C, -53°C, -54°C, -55°C, -56°C, -57°C, -58°C, -59°C or -60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In an optional embodiment, the freeze-drying time is 24 to 48 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours or 48 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] As a preferred technical solution of the present invention, in step (II), the heating temperature of the high temperature calcination is 750-850°C, for example, it can be 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In an optional embodiment, the holding time for high temperature calcination is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In an optional example, the acidification process includes: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite.

[0052] In an optional example, the concentration of the nitric acid solution is 8~12 mol / L, for example, it can be 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L, 10.5 mol / L, 11 mol / L, 11.5 mol / L or 12 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] The present invention particularly limits the concentration of the nitric acid solution to 8-12 mol / L, and the amount of aluminum ions dissolved increases with the increase of the concentration of the nitric acid solution, because the higher the concentration of hydrogen ions, the more favorable it is for adsorption on the sericite crystal surface, thereby destroying the Al-O bond and Si-O bond in the lamella lattice, and dissolving the aluminum ions in the tetrahedron and octahedron. Since the hydrogen ions first replace the cations such as potassium ions and sodium ions between the layers after entering the lamella, and then dissolve the aluminum ions and silicon ions with four-coordinate and six-coordinate coordination, therefore, in a high-concentration hydrogen ion environment, after the replacement and dissolution of part of the aluminum ions, there are still high-concentration hydrogen ions to promote the further dissolution of the aluminum ions. When the concentration of the nitric acid solution exceeds the upper limit of the range defined in the present invention, the dissolution efficiency of aluminum ions gradually decreases. This is related to the aluminum ion content in the sericite flakes and the aluminum ion concentration in the solution. As the nitric acid solution continuously dissolves aluminum ions, the concentration of aluminum ions in the surface layer of the sericite continues to decrease, while the concentration of aluminum ions in the solution near the contact surface continues to increase, prompting the replacement and aluminum ion dissolution to reach a chemical equilibrium, ultimately reducing the dissolution rate of aluminum ions.

[0054] In an optional example, the ratio of the activated sericite to the nitric acid solution is (2~4) g:100 mL, for example, it can be 2.0 g:100 mL, 2.2 g:100 mL, 2.4 g:100 mL, 2.6 g:100 mL, 2.8 g:100 mL, 3.0 g:100 mL, 3.2 g:100 mL, 3.4 g:100 mL, 3.6 g:100 mL, 3.8 g:100 mL or 4.0 g:100 mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In an optional example, the mixing and stirring time of the activated sericite and the nitric acid solution is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In an optional example, the temperature for mixing the activated sericite and the nitric acid solution is 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In an optional example, the lithiation process includes:

[0058] The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite.

[0059] In an optional example, the mass ratio of the acidified sericite to the lithium nitrate is 1:(8~10), for example, it can be 1:8.0, 1:8.2, 1:8.4, 1:8.6, 1:8.8, 1:9.0, 1:9.2, 1:9.4, 1:9.6, 1:9.8 or 1:10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In an optional embodiment, the calcination temperature of the mixed powder is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In an optional example, the calcination time of the mixed powder is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] The present invention particularly limits the calcination time of the mixed powder to 5 to 6 hours. When the calcination time is less than 5 hours, the lithium ions lack sufficient time to replace the interlayer cations, and the lithium modification effect is not ideal. As the reaction time increases, there is sufficient time for the ion exchange reaction, and the finally obtained lithiated sericite has a higher cation exchange capacity, which provides a sufficient number of exchangeable cations for the later organic intercalation modification, so that the organic intercalation modification can be carried out smoothly. When the calcination time exceeds 6 hours, the ion exchange reaction reaches equilibrium, and the number of exchangeable cations between the sericite sheets reaches saturation. Continuing to increase the calcination time will not only not increase the cation exchange concentration between the sericite sheets, but also affect the sheet structure of the sericite, so that the barrier property of the mica nanosheets is reduced, and the corrosion resistance of the paint film is affected.

[0063] As a preferred technical solution of the present invention, in step (II), the intercalation modification process includes:

[0064] The lithiated sericite is dispersed in deionized water to obtain a sericite solution, hexadecyltrimethylammonium bromide is added to the sericite solution, the mixture is stirred and heated, and then the intercalated sericite is obtained after filtering, washing and drying.

[0065] In an optional example, the mixing ratio of the lithiated sericite and deionized water is (0.8~1.3) g:100 mL, for example, it can be 0.8g:100mL, 0.85g:100mL, 0.9g:100mL, 0.95g:100mL, 1g:100mL, 1.05g:100mL, 1.1g:100mL, 1.15g:100mL, 1.2g:100mL, 1.25g:100mL or 1.3g:100mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In an optional example, the mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5~3.5), for example, it can be 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4 or 1:3.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] The present invention specifically limits the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution to 1:(2.5-3.5). With the increase of the amount of hexadecyltrimethylammonium bromide, the interlayer spacing of the mica nanosheets finally obtained shows a trend of first increasing and then decreasing. When the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide is within the numerical range defined by the present invention, a larger interlayer spacing can be obtained and a higher intercalation efficiency can be achieved. When the amount of hexadecyltrimethylammonium bromide is lower than the lower limit of the range defined by the present invention, the interlayer cations of the sericite cannot be completely exchanged by the hexadecyltrimethylammonium bromide chain, resulting in a smaller interlayer spacing of the intercalated sericite, and effective ultrasonic stripping cannot be achieved. When the amount of hexadecyltrimethylammonium bromide used exceeds the upper limit of the range defined in the present invention, too many organic chains tend to accumulate in the interlayer edge region of sericite, blocking the exchange channel between the organic chains and the interlayer cations, resulting in only a small number of hexadecyltrimethylammonium bromide molecular chains being able to successfully enter the interlayers of sericite, replacing lithium ions to achieve organic intercalation modification, while most of the hexadecyltrimethylammonium bromide molecular chains are unable to successfully enter the interlayers of sericite, but are simply adsorbed on the surface of sericite, resulting in low intercalation efficiency.

[0068] In an optional example, the mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] In an optional example, the temperature for mixing and stirring the sericite solution and hexadecyltrimethylammonium bromide is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] As a preferred technical solution of the present invention, in step (II), the ultrasonic peeling process includes:

[0071] The intercalated sericite is dispersed in ethanol, ultrasonically exfoliated to obtain a sericite dispersion, the sericite dispersion is centrifuged once, the supernatant after the first centrifugation is centrifuged twice, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets.

[0072] In an optional example, the mass ratio of the intercalated sericite to ethanol is 1:(4~5), for example, it can be 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In an optional example, the ultrasonic power of the ultrasonic peeling is 400~500W, for example, it can be 400W, 410W, 420W, 430W, 440W, 450W, 460W, 470W, 480W, 490W or 500W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] In an optional example, the ultrasonic time of the ultrasonic stripping is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0075] In an optional example, the rotation speed of the centrifugation is 2000~3000r / min, for example, it can be 2000r / min, 2100r / min, 2200r / min, 2300r / min, 2400r / min, 2500r / min, 2600r / min, 2700r / min, 2800r / min, 2900r / min or 3000r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0076] In an optional example, the centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In an optional example, the rotation speed of the secondary centrifugation is 2000-3000 r / min, for example, it can be 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min or 3000 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In an optional example, the secondary centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] As a preferred technical solution of the present invention, in step (II), the process of hydrophobic modification of the surface of the mica nanosheets comprises:

[0080] The mica nanosheets are dispersed in a silane coupling agent solution, mixed and stirred under a water bath heating condition to react, and after the reaction is completed, the modified mica nanosheets are obtained by filtering, washing and drying.

[0081] In an optional example, the silane coupling agent solution is prepared by the following method:

[0082] Anhydrous ethanol and distilled water are uniformly mixed in a volume ratio of (8-9):1 to obtain a mixed solvent, and an acetic acid solution is added dropwise to the mixed solvent to adjust the pH value thereof to 4.5-5.5; a silane coupling agent is added to the mixed solvent, and the mixture is mixed and stirred for 10-20 minutes to hydrolyze the silane coupling agent to obtain a silane coupling agent solution with a mass fraction of 3-5wt%.

[0083] The volume ratio of anhydrous ethanol to distilled water can be 8.0:1, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1 or 9.0:1, the pH value can be 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4 or 5.5, and the mixing time can be 10 min, 11 min, 12 min, 13 min , 14min, 15min, 16min, 17min, 18min, 19min or 20min, the mass fraction of the silane coupling agent solution can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In an optional example, the ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1g:(0.05~0.06)mL, for example, it can be 1g:0.05mL, 1g:0.051mL, 1g:0.052mL, 1g:0.053mL, 1g:0.054mL, 1g:0.055mL, 1g:0.056mL, 1g:0.057mL, 1g:0.058mL, 1g:0.059mL or 1g:0.06mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] The present invention particularly limits the ratio of mica nanosheets to the silane coupling agent in the silane coupling agent solution to 1 g: (0.05-0.06) mL. When the amount of the silane coupling agent exceeds the upper limit of the range defined by the present invention, the hydrophobic modification effect on the mica nanosheets will deteriorate. This is because when the amount of the silane coupling agent is too high, the silane coupling agent itself will undergo a polymerization reaction, resulting in a reduction in the amount of the silane coupling agent coupled and grafted with the mica nanosheets, and the hydrophobicity of the obtained modified mica nanosheets is reduced.

[0086] In an optional example, the mixing and stirring time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] In an optional example, the temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] As a preferred technical solution of the present invention, in step (III), the mass fraction of the composite modified nanocellulose in the composite suspension is 1-2wt%, for example, it can be 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] In an optional example, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:(3~5), for example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] The present invention particularly limits the mass ratio of composite modified nano cellulose and modified mica nano sheet to be 1: (3 ~ 5), the addition of composite modified nano cellulose can play its own mechanical strengthening effect, and can significantly improve the dispersibility of modified mica nano sheet in anticorrosive coating, avoid the modified mica nano sheet in anticorrosive coating to appear agglomeration, thereby causing stress concentration phenomenon, affecting the mechanical properties of paint film. However, the amount of composite modified nano cellulose should not be too high, when the amount of composite modified nano cellulose exceeds the upper limit of the range defined by the present invention, it will cause the viscosity of anticorrosive coating to be too high, which is not conducive to brushing construction. At the same time, the amount of modified mica nano sheet should not be too high, when the amount of modified mica nano sheet exceeds the upper limit of the range defined by the present invention, agglomeration phenomenon will still occur, thereby causing stress concentration phenomenon, affecting the mechanical properties of paint film.

[0091] In an optional example, the mass fraction of the nonionic surfactant in the composite suspension is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0092] In an optional example, the nonionic surfactant includes any one of ethoxylated fatty acid esters, alkanolamides, or fatty alcohol polyoxyethylene ethers, or a combination of at least two thereof.

[0093] In an optional embodiment, the ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500 W, for example, 400 W, 410 W, 420 W, 430 W, 440 W, 450 W, 460 W, 470 W, 480 W, 490 W or 500 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] In an optional example, the ultrasonic dispersion time of the composite suspension is 2 to 3 h, for example, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0095] In an optional example, the spray drying process of the composite dispersion is carried out in a spray drying tower.

[0096] In an optional embodiment, the inlet air temperature of the spray drying tower is 150-250°C, for example, it can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] In an optional embodiment, the outlet air temperature of the spray drying tower is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] In an optional embodiment, the feed rate of the spray drying tower is 50~100mL / h, for example, it can be 50mL / h, 55mL / h, 60mL / h, 65mL / h, 70mL / h, 75mL / h, 80mL / h, 85mL / h, 90mL / h, 95mL / h or 100mL / h, but is not limited to the listed values. In some optional embodiments, other unlisted values ​​within the numerical range are also applicable.

[0099] Compared to oven drying and freeze drying, the present invention particularly preferably uses a spray drying process, because the abundant hydroxyl functional groups on the surface of nanocellulose give it a high degree of hydrophilicity and gel-like properties, but also cause the nanocellulose to form irreversible agglomeration, i.e., "keratinization", during the oven drying process due to the action of intermolecular hydrogen bonds, thereby losing its nanometer size. The freeze-dried nanocellulose will form a sheet-like fiber flocculent, and it is also impossible to achieve uniform dispersion of a single nanocellulose. Compared to oven drying and freeze drying, spray drying can obtain fine nanocellulose powder and is simple and time-saving. The particle size after redispersion in the anti-corrosion coating remains almost unchanged compared to when it was not dried, and the unique advantages of nanocellulose can still be fully utilized.

[0100] In a second aspect, the present invention provides a composite reinforcing modifier for anti-corrosion coatings prepared by the preparation method described in the first aspect.

[0101] Compared with the prior art, the present invention has the following beneficial effects:

[0102] The present invention compounds the composite modified nanocellulose and modified mica nanosheets to prepare a composite reinforcing modifier for anticorrosive coatings, which can significantly improve the mechanical properties and corrosion resistance of the paint film. In the anticorrosive coating, the modified mica nanosheets tend to be arranged parallel to the surface of the paint film. Since the modified mica nanosheets are sheet-like structures, they are elastic and can slide, which can prevent the paint film from cracking due to stress concentration; at the same time, the modified mica nanosheets can form a layer of inert, solid and flexible protective film on the surface of the paint film that is resistant to chemical corrosion and sunlight radiation. This protective film can effectively prevent the penetration of the atmosphere and moisture, thereby playing a barrier and protective role on the base material. Combined with the mechanical enhancement properties of the composite modified nanocellulose itself, on the one hand, a three-dimensional network structure skeleton can be formed inside the paint film, and on the other hand, the dispersion uniformity of the modified mica nanosheets in the anticorrosive coating can be significantly improved. The synergistic effect between the composite modified nanocellulose and the modified mica nanosheets can significantly improve the mechanical properties and corrosion resistance of the paint film. BRIEF DESCRIPTION OF THE DRAWINGS

[0103] Figure 1 A flow chart of the preparation process of the composite reinforcing modifier provided in Examples 1-5 of the present invention;

[0104] Figure 2 This is a transmission electron microscope image of the nanocellulose used in Example 1 of the present invention;

[0105] Figure 3 This is a transmission electron microscopy image of the modified nanocellulose prepared in Example 1 of the present invention;

[0106] Figure 4 This is a transmission electron microscope image of the composite modified nanocellulose prepared in Example 1 of the present invention;

[0107] Figure 5 This is a scanning electron microscope image of the sericite mica used in Example 1 of the present invention;

[0108] Figure 6 This is a scanning electron microscope image of the activated sericite prepared in Example 1 of the present invention;

[0109] Figure 7 This is a scanning electron microscope image of the acidified sericite prepared in Example 1 of the present invention;

[0110] Figure 8 The infrared spectra of sericite and mica nanosheets prepared in Example 1 of the present invention are shown;

[0111] Fig. 9 Polarization curves of the paint films provided in Example 1 of the present invention and the comparative example. DETAILED DESCRIPTION

[0112] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0113] Example 1

[0114] This embodiment provides a method for preparing a composite reinforcing modifier for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0115] (1) under heating conditions of 40° C., nanocellulose and N,N'-carbonyldiimidazole solution were mixed and stirred for 12 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.2 mol / L, the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1, and after the reaction was completed, an intermediate product solution was obtained;

[0116] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.2 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.1, mixing and stirring at 40° C. for 12 hours to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;

[0117] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified nanocellulose to the dopamine in the dopamine solution is 100:8, mixed and stirred at 40°C for 24 hours to react, and after the reaction is completed, centrifuged at a speed of 6000 r / min for 30 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -50°C for 48 hours to obtain a composite modified nanocellulose;

[0118] (2) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 750°C and the holding time is 2 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 8 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2 g:100 mL, and the mixture is mixed and stirred at 80°C for 5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are uniformly mixed in a mass ratio of 1:8 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 300°C for 6 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0119] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 0.8 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.5, mixing and stirring at 70° C. for 3 h, and then filtering, washing and drying to obtain intercalated sericite;

[0120] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4, ultrasonic peeling was performed at an ultrasonic power of 400 W for 3 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2000 r / min, the time of the first centrifugation was 20 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2000 r / min, the time of the second centrifugation was 20 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0121] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 4.5; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 10 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 3wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.05mL, and the mixture was mixed and stirred for 60 minutes under a water bath heating condition of 70°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;

[0122] (3) The composite modified nanocellulose obtained in step (1), the modified mica nanosheets obtained in step (2), the ethoxylated fatty acid ester and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the composite modified nanocellulose in the composite suspension is 1wt%, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:3, the mass fraction of the ethoxylated fatty acid ester in the composite suspension is 0.5wt%, and the composite suspension is ultrasonically dispersed at an ultrasonic power of 400 W for 3 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 150° C., the outlet air temperature is 90° C., and the feeding speed is 50 mL / h, and the composite reinforcing modifier is obtained after spray drying.

[0123] Figure 2 , Figure 3 and Figure 4 The transmission electron microscope images of the nanocellulose used in this example, the modified nanocellulose prepared in this example, and the composite modified nanocellulose are shown in FIG. Figure 2 It can be seen that the nanocellulose used in this embodiment presents an intertwined network structure. This is because the nanocellulose molecular chains without any modification contain a large number of hydroxyl functional groups, and it is easy to form a high-energy hydrogen bond network between the molecular chains. Therefore, the nanocellulose molecular chains are very easy to agglomerate, usually existing in the form of a network and unevenly distributed in a certain area. Figure 3 It can be seen that the dispersion uniformity of the modified nanocellulose obtained by CDI-amino grafting modification is improved. Figure 4 It can be seen that a rough structure is formed on the surface of the composite modified nanocellulose, which is formed by the deposition of polydopamine obtained after oxidative self-polymerization of dopamine on the surface of the modified nanocellulose.

[0124] Figure 5 , Figure 6 and Figure 7The scanning electron microscope images of the sericite used in this embodiment, the activated sericite prepared in this embodiment and the acidified sericite are shown in FIG. Figure 5 , the activated sericite obtained after high temperature activation treatment (such as Figure 6 The surface of the quartz crystal (as shown in Figure 2) has a rough structure, but the crystal structure is not completely destroyed and the lamellae morphology remains intact. Figure 6 , the acidified sericite (such as Figure 7 The lamella structure of the sericite mica is complete, the surface roughness structure has increased, wrinkles and cracks appear on the surface, and the surface area of ​​the sericite mica lamellae is increased, which is beneficial to the adsorption of lithium ions and cation exchange during the lithiation process.

[0125] Figure 8 The infrared spectra of sericite and mica nanosheets prepared in this example are shown in the figure. It can be seen from the figure that 3622cm -1 and 3448cm -1 The stretching vibration peaks of free water between sericite layers and free -OH on the surface are 1028 cm -1 The peak corresponding to the stretching vibration of Si-O-Si skeleton of sericite is 400~800cm -1 The corresponding Al-O and Si-O bending vibration peaks are found in the infrared spectra of sericite and mica nanosheets, indicating that both contain sericite. The difference is that new characteristic peaks appear in the infrared spectra of mica nanosheets, such as: 2918cm -1 and 2851cm -1 The corresponding positions are the antisymmetric -CH 3 and -CH 2 - stretching vibration peak, 1487cm -1 The peak at 1640 cm corresponds to the bending vibration peak of CN in the molecular chain of hexadecyltrimethylammonium bromide. -1 The corresponding CC absorption vibration peak is shown in Figure 2. The newly appeared characteristic peaks indicate that the hexadecyltrimethylammonium bromide molecular chain has entered the sericite mica layer. In addition, the intensity of some peaks in the infrared spectrum of mica nanosheets has changed, such as: 3622cm -1 The peak intensity at 3448cm -1 The peak intensity at 1028cm is enhanced, which is due to the fact that the mica nanosheets modified by organic intercalation change from hydrophilic to hydrophobic, resulting in less free water between the layers; -1 The peak intensity at 4° is weakened because the molecular chain of hexadecyltrimethylammonium bromide enters the interlayers of sericite and destroys the skeleton structure to a certain extent.

[0126] Example 2

[0127] This embodiment provides a method for preparing a composite reinforcing modifier for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0128] (1) under heating conditions of 42° C., nanocellulose and N,N'-carbonyldiimidazole solution were mixed and stirred for 11.5 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.22 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.05, and an intermediate product solution was obtained after the reaction was completed;

[0129] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.22 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.12, mixing and stirring at 42° C. for 11.5 hours to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;

[0130] Dopamine was dissolved in deionized water to obtain a mixed solution with a concentration of 1.2 g / L, and Tris-HCl buffer was added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified nanocellulose was dispersed in the dopamine solution, the mass ratio of the modified nanocellulose to the dopamine in the dopamine solution was 100:8.5, mixed and stirred at 42° C. for 21 hours to react, and after the reaction was completed, centrifuged at a speed of 6500 r / min for 28 minutes, the precipitate was washed, and the washed precipitate was freeze-dried at -52° C. for 42 hours to obtain a composite modified nanocellulose;

[0131] (2) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 780°C and the holding time is 1.8 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 9 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2.5 g:100 mL, and the mixture is mixed and stirred at 82°C for 4.8 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:8.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 320°C for 5.8 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0132] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.8, mixing and stirring at 72° C. for 2.8 h, and then filtering, washing and drying to obtain intercalated sericite;

[0133] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.2, ultrasonic stripping was performed at an ultrasonic power of 420 W for 2.8 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2200 r / min, the time of the first centrifugation was 18 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2200 r / min, the time of the second centrifugation was 18 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0134] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.2:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 4.8; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 12 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 3.5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.052mL, and the mixture was mixed and stirred for 50 minutes under a water bath heating condition of 72°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;

[0135] (3) The composite modified nanocellulose obtained in step (1), the modified mica nanosheets obtained in step (2), the ethoxylated fatty acid ester and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the composite modified nanocellulose in the composite suspension is 1.2wt%, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:3.5, the mass fraction of the ethoxylated fatty acid ester in the composite suspension is 0.8wt%, and the composite suspension is ultrasonically dispersed at an ultrasonic power of 420 W for 2.8 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 180° C., the outlet air temperature is 92° C., and the feeding speed is 60 mL / h, and the composite reinforcing modifier is obtained after spray drying.

[0136] Example 3

[0137] This embodiment provides a method for preparing a composite reinforcing modifier for anticorrosive coatings, such as Figure 1As shown, the preparation method specifically comprises the following steps:

[0138] (1) under heating conditions of 45° C., nanocellulose and N,N'-carbonyldiimidazole solution were mixed and stirred for 11 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.25 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.1, and after the reaction was completed, an intermediate product solution was obtained;

[0139] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.25 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.15, mixing and stirring at 45° C. for 11 hours to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;

[0140] Dopamine was dissolved in deionized water to obtain a mixed solution with a concentration of 1.5 g / L, and Tris-HCl buffer was added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified nanocellulose was dispersed in the dopamine solution, the mass ratio of the modified nanocellulose to the dopamine in the dopamine solution was 100:9, mixed and stirred at 45° C. for 18 hours to react, and after the reaction was completed, centrifuged at a speed of 7000 r / min for 25 minutes, the precipitate was washed, and the washed precipitate was freeze-dried at -55° C. for 38 hours to obtain a composite modified nanocellulose;

[0141] (2) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 800°C and the holding time is 1.5 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 10 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3 g:100 mL, and the mixture is mixed and stirred at 85°C for 4.5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly in a mass ratio of 1:9 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 350°C for 5.5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0142] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3, mixing and stirring at 75°C for 2.5 hours, and then filtering, washing and drying to obtain intercalated sericite;

[0143] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.5, ultrasonic stripping was performed at an ultrasonic power of 450 W for 2.5 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2500 r / min, the time of the first centrifugation was 15 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2500 r / min, the time of the second centrifugation was 15 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0144] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.5:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 15 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 4wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.055mL, and the mixture was mixed and stirred for 40 minutes under a water bath heating condition of 75°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;

[0145] (3) The composite modified nanocellulose obtained in step (1), the modified mica nanosheets obtained in step (2), alkanolamide and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the composite modified nanocellulose in the composite suspension is 1.5wt%, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:4, the mass fraction of the alkanolamide in the composite suspension is 1wt%, and the composite suspension is ultrasonically dispersed at an ultrasonic power of 450W for 2.5h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 200°C, the outlet air temperature is 95°C, and the feeding speed is 70mL / h, and the composite reinforcing modifier is obtained after spray drying.

[0146] Example 4

[0147] This embodiment provides a method for preparing a composite reinforcing modifier for anticorrosive coatings, such as Figure 1As shown, the preparation method specifically comprises the following steps:

[0148] (1) under heating conditions of 48° C., mixing and stirring nanocellulose and N,N'-carbonyldiimidazole solution for 10.5 h to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.28 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.15, and after the reaction is completed, an intermediate product solution is obtained;

[0149] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.28 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.18, mixing and stirring at 48° C. for 10.5 hours to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;

[0150] Dopamine was dissolved in deionized water to obtain a mixed solution with a concentration of 1.8 g / L, and Tris-HCl buffer was added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified nanocellulose was dispersed in the dopamine solution, the mass ratio of the modified nanocellulose to the dopamine in the dopamine solution was 100:9.5, mixed and stirred at 48°C for 15 hours to react, and after the reaction was completed, centrifuged at a speed of 7500 r / min for 23 minutes, the precipitate was washed, and the washed precipitate was freeze-dried at -58°C for 32 hours to obtain a composite modified nanocellulose;

[0151] (2) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 820°C and the holding time is 1.2 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 11 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3.5 g:100 mL, and the mixture is mixed and stirred at 88°C for 4.2 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:9.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 380°C for 5.2 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0152] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.2 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.2, mixing and stirring at 78° C. for 2.2 h, and then filtering, washing and drying to obtain intercalated sericite;

[0153] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.8, ultrasonic stripping was performed at an ultrasonic power of 480 W for 2.2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2800 r / min, the time of the first centrifugation was 12 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2800 r / min, the time of the second centrifugation was 12 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0154] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.8:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5.2; silane coupling agent KH560 was added to the mixed solvent, and the mixture was mixed and stirred for 18 minutes to hydrolyze the silane coupling agent KH560 to obtain a silane coupling agent solution with a mass fraction of 4.5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH560 in the silane coupling agent solution was 1g:0.058mL, and the mixture was mixed and stirred for 40 minutes under a water bath heating condition of 78°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;

[0155] (3) The composite modified nanocellulose obtained in step (1), the modified mica nanosheets obtained in step (2), the fatty alcohol polyoxyethylene ether and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the composite modified nanocellulose in the composite suspension is 1.8wt%, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:4.5, and the mass fraction of the fatty alcohol polyoxyethylene ether in the composite suspension is 1.2wt%. The composite suspension is ultrasonically dispersed at an ultrasonic power of 480 W for 2.2 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 220° C., the outlet air temperature is 98° C., and the feeding speed is 80 mL / h. After spray drying, the composite reinforcing modifier is obtained.

[0156] Example 5

[0157] This embodiment provides a method for preparing a composite reinforcing modifier for anticorrosive coatings, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0158] (1) under heating conditions of 50° C., nanocellulose and N,N'-carbonyldiimidazole solution were mixed and stirred for 10 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.3 mol / L, and the mass ratio of nanocellulose to N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.2, and an intermediate product solution was obtained after the reaction was completed;

[0159] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.3 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.2, mixing and stirring at 50° C. for 10 hours to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose;

[0160] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 2 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified nanocellulose to the dopamine in the dopamine solution is 100:10, mixed and stirred at 50° C. for 12 hours to react, and after the reaction is completed, centrifuged at a speed of 8000 r / min for 20 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -60° C. for 24 hours to obtain a composite modified nanocellulose;

[0161] (2) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 850°C and the holding time is 1 hour, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 12 mol / L, and the ratio of the activated sericite to the nitric acid solution is 4 g:100 mL, and the mixture is mixed and stirred at 90°C for 4 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:10 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 400°C for 5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;

[0162] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.3 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.5, mixing and stirring at 80° C. for 2 h, and then filtering, washing and drying to obtain intercalated sericite;

[0163] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:5, ultrasonic peeling was performed at an ultrasonic power of 500 W for 2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 3000 r / min, the time of the first centrifugation was 10 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 3000 r / min, the time of the second centrifugation was 10 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;

[0164] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 9:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5.5; a silane coupling agent KH560 was added to the mixed solvent, and the mixture was mixed and stirred for 20 minutes to hydrolyze the silane coupling agent KH560 to obtain a silane coupling agent solution with a mass fraction of 5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of the mica nanosheets to the silane coupling agent KH560 in the silane coupling agent solution was 1g:0.06mL, and the mixture was mixed and stirred for 30 minutes under a water bath heating condition of 80°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;

[0165] (3) The composite modified nanocellulose obtained in step (1), the modified mica nanosheets obtained in step (2), the fatty alcohol polyoxyethylene ether and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the composite modified nanocellulose in the composite suspension is 2wt%, the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is 1:5, and the mass fraction of the fatty alcohol polyoxyethylene ether in the composite suspension is 1.5wt%. The composite suspension is ultrasonically dispersed at an ultrasonic power of 500 W for 2 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 250° C., the outlet air temperature is 100° C., and the feeding speed is 100 mL / h. After spray drying, the composite reinforcing modifier is obtained.

[0166] Example 6

[0167] This embodiment provides a method for preparing a composite reinforcing modifier for an anti-corrosion coating. The difference from Embodiment 1 is that in step (1), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:1, and the other process parameters and operating steps are exactly the same as those in Embodiment 1.

[0168] Example 7

[0169] This embodiment provides a method for preparing a composite reinforcing modifier for an anti-corrosion coating. The difference from Embodiment 1 is that in step (1), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:1.5, and the other process parameters and operating steps are exactly the same as those in Embodiment 1.

[0170] Example 8

[0171] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (1), the concentration of dopamine in the mixed solution is adjusted to 0.5 g / L, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0172] Example 9

[0173] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (1), the concentration of dopamine in the mixed solution is adjusted to 2.5 g / L, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0174] Example 10

[0175] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (2), the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is adjusted to 1:2, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0176] Embodiment 11

[0177] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (2), the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is adjusted to 1:4, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0178] Example 12

[0179] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (3), the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is adjusted to 1:2, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0180] Embodiment 13

[0181] This embodiment provides a method for preparing a composite reinforcing modifier for anti-corrosion coatings. The difference from Embodiment 1 is that in step (3), the mass ratio of the composite modified nanocellulose to the modified mica nanosheets is adjusted to 1:6, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0182] Application Examples

[0183] This application example provides a method for preparing an anti-corrosion coating, which specifically includes the following steps:

[0184] 0.3wt% of dispersant SRE-4190, 0.5wt% of 2093 transparent epoxy defoamer, 0.2wt% of Digo 270 wetting agent and 0.2wt% of Digo 450 leveling agent were sequentially added to DY-601 waterborne epoxy emulsion, and stirred at low speed for 10-15min to obtain a mixed solution; at room temperature, the composite reinforcing modifier prepared in the embodiment of the present invention was added to the mixed solution, and the mixture was ground and filtered after high-speed stirring for 1-1.5h to obtain component A;

[0185] Weigh a certain amount of DY-330 anti-flash rust agent and add it dropwise to DY-175 epoxy curing agent, stir evenly to obtain component B, in which the mass fraction of DY-330 anti-flash rust agent in component B is 0.5wt%;

[0186] According to the mass ratio of component A to component B being 3:1, component B is added to component A, and the mixture is stirred evenly to obtain an anti-corrosion coating.

[0187] According to the preparation method provided in this application example, anti-corrosion coatings were prepared using the composite reinforcing modifiers provided in Examples 1-13, and were named anti-corrosion coating 1, anti-corrosion coating 2, anti-corrosion coating 3, anti-corrosion coating 4, anti-corrosion coating 5, anti-corrosion coating 6, anti-corrosion coating 7, anti-corrosion coating 8, anti-corrosion coating 9, anti-corrosion coating 10, anti-corrosion coating 11, anti-corrosion coating 12 and anti-corrosion coating 13 (hereinafter referred to as anti-corrosion coatings 1-13).

[0188] Comparative Example

[0189] This comparative example provides a method for preparing a blank coating, which specifically comprises the following steps:

[0190] 0.3wt% of dispersant SRE-4190, 0.5wt% of 2093 transparent epoxy defoamer, 0.2wt% of Digo 270 wetting agent and 0.2wt% of Digo 450 leveling agent were sequentially added to DY-601 waterborne epoxy emulsion, stirred at high speed for 1-1.5h, and then ground and filtered to obtain component A;

[0191] Weigh a certain amount of DY-330 anti-flash rust agent and add it dropwise to DY-175 epoxy curing agent, stir evenly to obtain component B, in which the mass fraction of DY-330 anti-flash rust agent in component B is 0.5wt%;

[0192] According to the mass ratio of component A to component B being 3:1, component B was added to component A and stirred evenly to obtain a blank coating.

[0193] The anticorrosive coatings 1-13 prepared in Examples 1-13 and the blank coatings provided in the comparative example were coated, and the specific operation steps were as follows:

[0194] (1) Grind the tinplate sample. Grind it several times in one direction with 800-grit sandpaper, rotate it 90° and continue grinding. Rinse the stains on the surface of the tinplate sample with ethanol, wipe it with absorbent cotton and then clean it with acetone. Blow dry the sample with a hair dryer, and finally rinse it with anhydrous ethanol several times and dry it for later use.

[0195] (2) Fix the cleaned tinplate sample on a horizontal table, and use a wire rod to evenly roll the anti-corrosion coating and blank coating on the surface of the tinplate sample. After rolling, let it stand at room temperature. After the coating surface is dry, place it in an oven at 60°C to dry for 12 hours. After standing for two days, test it.

[0196] The properties of the paint films formed by the anti-corrosion coating and the blank coating were tested. The specific test steps are as follows:

[0197] (1) Pencil hardness test

[0198] The scratch hardness method was adopted and the pencil hardness of the paint film on the surface of the tinplate sample was tested in accordance with the national standard GB / T6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes".

[0199] (2) Corrosion resistance test

[0200] The paint film was tested using a CHI760E electrochemical workstation. The electrolyte was a 3.5wt% NaCl solution, and the tinplate samples coated with different paint films were subjected to electrochemical impedance spectroscopy (EIS) tests. The apparent area of ​​the working electrode was 1cm×1cm, the saturated calomel electrode was the reference electrode, and the 2cm×2cm platinum sheet was the counter electrode, forming a three-electrode test system. After the system to be tested was stable, a polarization curve test was performed to compare the corrosion potential and current of different paint films to analyze the degree and rate of corrosion. The scanning rate of the polarization curve test was 1mV / s, and the test voltage range was OCP±300mV. The corrosion current density (Icorr) and corrosion potential (Ecorr) of the paint film were obtained by the polarization curve. The lower corrosion current density (Icorr) and higher corrosion potential (Ecorr) indicate that the paint film has better corrosion resistance.

[0201] The polarization curves of the paint films formed in Example 1 and the comparative example are as follows: Fig. 9 As shown in the figure, it can be seen that the corrosion potential of the paint film formed in Example 1 is higher than that of the comparative example, while the corrosion current density is lower than that of the comparative example, which indicates that the composite reinforcing modifier provided in Example 1 can significantly improve the corrosion resistance of the paint film.

[0202] The test results of the pencil hardness, corrosion potential and corrosion current density of the paint film are shown in Table 1.

[0203] Table 1

[0204] Pencil hardness Corrosion potential Ecorr (V) <![CDATA[Corrosion current density Icorr (A / cm 2 ).]]> Example 1 3H -0.411 <![CDATA[1.285×10 -6 ]]> Example 2 3H -0.387 <![CDATA[1.273×10 -6 ]]> Example 3 4H -0.376 <![CDATA[1.268×10 -6 ]]> Example 4 4H -0.369 <![CDATA[1.260×10 -6 ]]> Example 5 4H -0.348 <![CDATA[1.254×10 -6 ]]> Example 6 HB -0.452 <![CDATA[1.348×10 -6 ]]> Example 7 2H -0.423 <![CDATA[1.304×10 -6 ]]> Example 8 H -0.438 <![CDATA[1.326×10 -6 ]]> Example 9 2H -0.419 <![CDATA[1.292×10 -6 ]]> Example 10 HB -0.475 <![CDATA[1.353×10 -6 ]]> Embodiment 11 H -0.426 <![CDATA[1.315×10 -6 ]]> Example 12 HB -0.493 <![CDATA[1.367×10 -6 ]]> Embodiment 13 B -0.480 <![CDATA[1.358×10 -6 ]]> Comparative Example 2B -0.507 <![CDATA[2.090×10 -6 ]]>

[0205] It can be seen from the test data provided in Table 1 that the pencil hardness of the paint films prepared in Examples 1-5 is higher than that of Examples 6-13 and the comparative example, which indicates that the composite reinforcing modifier provided by the present invention can significantly improve the mechanical properties of the paint films. In addition, the corrosion potential of the paint films prepared in Examples 1-5 is higher than that of Examples 6-13 and the comparative example, and the corrosion current density is lower than that of Examples 6-13 and the comparative example, which indicates that the composite reinforcing modifier provided by the present invention can significantly improve the corrosion resistance of the paint films.

[0206] It can be seen from the test data of Example 1, Example 6 and Example 7 that the pencil hardness of the paint film of Example 6 and Example 7 is lower than that of Example 1, the corrosion potential is lower than that of Example 1, and the corrosion current density is higher than that of Example 1. This is because the amount of octadecylamine used in Example 6 is too small, and the grafting rate of octadecylamine is too low, which affects the dispersibility of the composite modified nanocellulose in the anticorrosive coating, and ultimately affects the mechanical properties and corrosion resistance of the paint film. In Example 7, the amount of octadecylamine used is too large, and the octadecylamine that is not grafted to the nanocellulose molecular chain will be deposited on the surface of the nanocellulose, making the hydrophobicity of the composite modified nanocellulose too high, affecting its compatibility with the resin emulsion, causing the composite modified nanocellulose to settle and stratify in the anticorrosive coating, and ultimately resulting in reduced mechanical properties and corrosion resistance of the paint film.

[0207] It can be seen from the test data of Example 1, Example 8 and Example 9 that the pencil hardness of the paint film of Example 8 and Example 9 is lower than that of Example 1, the corrosion potential is lower than that of Example 1, and the corrosion current density is higher than that of Example 1. This is because the concentration of dopamine in Example 8 is too low, and the polydopamine produced is less, which is not enough to cover all the hydrophobic long chains of octadecylamine on the surface of the modified nanocellulose. During the high-speed dispersion process, the hydrophobic long chains of octadecylamine grafted on the surface of the modified nanocellulose are easy to fall off, which reduces the dispersibility of the composite modified nanocellulose in the anticorrosive coating, and ultimately affects the mechanical properties and corrosion resistance of the paint film. The concentration of dopamine in Example 9 is too high, exceeding the equilibrium adsorption value, resulting in the desorption of polydopamine adsorbed on the surface of the modified nanocellulose, which also affects the reinforcement effect of octadecylamine, resulting in the reduction of the dispersibility of the composite modified nanocellulose in the anticorrosive coating, and the mechanical properties and corrosion resistance of the paint film.

[0208] It can be seen from the test data of Example 1, Example 10 and Example 11 that the pencil hardness of the paint film of Example 10 and Example 11 is lower than that of Example 1, the corrosion potential is lower than that of Example 1, and the corrosion current density is higher than that of Example 1. This is because the amount of hexadecyltrimethylammonium bromide in Example 10 is too small, the interlayer cations of sericite cannot be completely exchanged by the hexadecyltrimethylammonium bromide chain, and effective ultrasonic stripping cannot be achieved, resulting in the inability to fully exert the barrier capacity of the mica nanosheets, thereby affecting the corrosion resistance of the paint film. At the same time, the nano mica sheets that have not been fully stripped will agglomerate in the anti-corrosion coating, which will also affect the mechanical properties of the paint film to a certain extent. The excessive amount of hexadecyltrimethylammonium bromide in Example 11 will block the exchange channel between the organic chain and the interlayer cations, thereby hindering the ultrasonic stripping of sericite, making it impossible to fully exert the barrier capacity of the mica nanosheets, thereby affecting the corrosion resistance of the paint film. At the same time, the nano mica sheets that have not been fully stripped will agglomerate in the anti-corrosion coating, which will also affect the mechanical properties of the paint film to a certain extent.

[0209] It can be seen from the test data of Example 1, Example 12 and Example 13 that the pencil hardness of the paint film of Example 12 and Example 13 is lower than that of Example 1, the corrosion potential is lower than that of Example 1, and the corrosion current density is higher than that of Example 1. This is because the amount of modified mica nanosheets in Example 12 is too small, and the proportion of composite modified nanocellulose is relatively too high, which will lead to too high viscosity of the anticorrosive coating, and the modified mica nanosheets cannot be evenly dispersed in the anticorrosive coating, which ultimately affects the mechanical properties and corrosion resistance of the paint film. In Example 13, the amount of mica nanosheets is too much, and the proportion of composite modified nanocellulose is relatively too low. Excessive mica nanosheets will agglomerate in the anticorrosive coating, and their barrier ability cannot be fully exerted, thereby affecting the corrosion resistance of the paint film. At the same time, too low an amount of composite modified nanocellulose will also affect the mechanical properties of the paint film.

[0210] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite reinforcing modifier for anticorrosive coatings, characterized in that: The preparation method comprises: (I) mixing nanocellulose and N,N'-carbonyldiimidazole solution, stirring and heating to react, and obtaining an intermediate product solution after the reaction is completed; adding octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain modified nanocellulose; dispersing the modified nanocellulose in dopamine solution, mixing, stirring and heating to react, and centrifuging, washing and freeze-drying after the reaction is completed to obtain composite modified nanocellulose; (II) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets; subjecting the mica nanosheets to surface hydrophobic modification with a silane coupling agent to obtain modified mica nanosheets; (III) mixing the composite modified nanocellulose obtained in step (I), the modified mica nanosheets obtained in step (II), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the composite reinforcing modifier.

2. The preparation method according to claim 1, characterized in that: In step (I), the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane; The concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2-0.3 mol / L; The mass ratio of the nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1-1.2); The mixing and stirring time of the nanocellulose and the N,N'-carbonyldiimidazole solution is 10 to 12 hours; The temperature for mixing and stirring the nanocellulose and the N,N'-carbonyldiimidazole solution is 40-50°C.

3. The preparation method according to claim 1, characterized in that: In step (I), the octadecylamine solution is composed of octadecylamine and dichloromethane; The concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L; The molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1.1-1.2); The mixing and stirring time of the intermediate product solution and the octadecylamine solution is 10 to 12 hours; The temperature of mixing and stirring the intermediate product solution and the octadecylamine solution is 40-50°C.

4. The preparation method according to claim 1, characterized in that: In step (I), the dopamine solution is prepared by the following method: Dissolving dopamine in deionized water to obtain a mixed solution with a concentration of 1-2 g / L, adding Tris-HCl buffer to the mixed solution to adjust the pH value of the mixed solution to 8.5, thereby obtaining the dopamine solution; The mass ratio of the modified nanocellulose to the dopamine in the dopamine solution is 100:(8-10); The modified nanocellulose and dopamine solution are mixed and stirred for 12 to 24 hours; The temperature of mixing and stirring the modified nanocellulose and the dopamine solution is 40-50° C.; The centrifugal speed is 6000-8000 r / min; The centrifugal time is 20 to 30 minutes; The freeze drying temperature is -50 to -60°C; The freeze-drying time is 24 to 48 hours.

5. The preparation method according to claim 1, characterized in that: In step (II), the heating temperature of the high temperature calcination is 750-850°C; The holding time of the high temperature calcination is 1 to 2 hours; The acidification process comprises: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite; The concentration of the nitric acid solution is 8-12 mol / L; The ratio of the activated sericite to the nitric acid solution is (2-4) g:100 mL; The time for mixing and stirring the activated sericite and the nitric acid solution is 4 to 5 hours; The temperature of mixing and stirring the activated sericite and the nitric acid solution is 80-90° C.; The lithiation process comprises: The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite; The mass ratio of the acidified sericite to the lithium nitrate is 1:(8-10); The calcination temperature of the mixed powder is 300-400°C; The calcination time of the mixed powder is 5 to 6 hours.

6. The preparation method according to claim 1, characterized in that: In step (II), the intercalation modification process includes: Dispersing the lithiated sericite in deionized water to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the intercalated sericite; The mixing ratio of the lithiated sericite and deionized water is (0.8-1.3) g:100 mL; The mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5-3.5); The mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours; The temperature for mixing and stirring the sericite solution and cetyltrimethylammonium bromide is 70-80°C.

7. The preparation method according to claim 1, characterized in that: In step (II), the ultrasonic peeling process includes: The intercalated sericite is dispersed in ethanol, and ultrasonic stripping is performed to obtain a sericite dispersion liquid, the sericite dispersion liquid is centrifuged once, the supernatant after the first centrifugation is taken for a second centrifugation, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets; The mass ratio of the intercalated sericite to ethanol is 1:(4-5); The ultrasonic power of the ultrasonic peeling is 400-500W; The ultrasonic peeling time is 2 to 3 hours; The rotation speed of the primary centrifugation is 2000-3000 r / min; The time of one centrifugation is 10 to 20 minutes; The secondary centrifugation speed is 2000-3000 r / min; The secondary centrifugation time is 10 to 20 minutes.

8. The preparation method according to claim 1, characterized in that: In step (II), the process of hydrophobic modification of the surface of the mica nanosheets comprises: Dispersing the mica nanosheets in a silane coupling agent solution, mixing and stirring under a water bath heating condition to react, and filtering, washing and drying after the reaction to obtain the modified mica nanosheets; The silane coupling agent solution is prepared by the following method: Anhydrous ethanol and distilled water are uniformly mixed in a volume ratio of (8-9):1 to obtain a mixed solvent, and an acetic acid solution is added dropwise to the mixed solvent to adjust the pH value thereof to 4.5-5.5; a silane coupling agent is added to the mixed solvent, and the mixture is stirred for 10-20 minutes to hydrolyze the silane coupling agent to obtain a silane coupling agent solution with a mass fraction of 3-5 wt %; The ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1 g: (0.05-0.06) mL; The mixing time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes; The temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C.

9. The preparation method according to claim 1, characterized in that: In step (III), the mass fraction of the composite modified nanocellulose in the composite suspension is 1-2wt%; The mass ratio of the composite modified nanocellulose to the modified mica nanosheet is 1:(3-5); The mass fraction of the nonionic surfactant in the composite suspension is 0.5-1.5wt%; The nonionic surfactant includes any one or a combination of at least two of ethoxylated fatty acid esters, alkanolamides or fatty alcohol polyoxyethylene ethers; The ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500W; The ultrasonic dispersion time of the composite suspension is 2 to 3 hours; The spray drying process of the composite dispersion is carried out in a spray drying tower; The air inlet temperature of the spray drying tower is 150-250°C; The outlet air temperature of the spray drying tower is 90-100°C; The feeding speed of the spray drying tower is 50-100 mL / h.

10. A composite reinforcing modifier for anti-corrosion coatings prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nano-cellulose modified acrylic resin, preparation method thereof and decorative paper

    CN112144316A

  • Modified sericite-epoxy resin composite paint and preparation method thereof, and preparation method of composite coating thereof

    CN113402945A

  • Water-based anticorrosive coating applied to deep sea environment as well as preparation method and application of water-based anticorrosive coating

    CN113549386A

  • Super-hydrophobic modification method of nanocellulose

    CN113773404A

  • Anti-corrosion coating for highway bridge anti-collision guardrail and preparation method of anti-corrosion coating

    CN116004113A